2012
DOI: 10.1001/2013.jamaneurol.79
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Jakob-Creutzfeldt Disease

Abstract: To identify the misdiagnoses of patients with sporadic Jakob-Creutzfeldt disease (sCJD) during the course of their disease and determine which medical specialties saw patients with sCJD prior to the correct diagnosis being made and at what point in the disease course a correct diagnosis was made.Design: Retrospective medical record review.Setting: A specialty referral center of a tertiary academic medical center.Participants: One hundred sixty-three serial patients over a 5.5-year period who ultimately had pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 32 publications
1
58
0
2
Order By: Relevance
“…MRI is a tool that is increasingly useful in the evaluation and early detection of suspected CJD and excluding other diseases, which may possibly be treatable (31,32). A retrospective study suggested that basal ganglia, subcortical signal intensity changes and cortical ribboning on DWI are the most important imaging markers (33).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a tool that is increasingly useful in the evaluation and early detection of suspected CJD and excluding other diseases, which may possibly be treatable (31,32). A retrospective study suggested that basal ganglia, subcortical signal intensity changes and cortical ribboning on DWI are the most important imaging markers (33).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]9 Brain MRI is a critical diagnostic tool with higher sensitivity and specificity than traditional biomarkers such as CSF 14-3-3 protein and EEG. 10,11 FLAIR and DWI sequences typically demonstrate hyperintensities involving the cortex, striatum, and/or thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…At our center, a thorough laboratory evaluation for causes of RPD [4][5][6] was unrevealing. This included erythrocyte sedimentation rate, antinuclear antibody, anti-neutrophil cytoplasmic antibodies (ANCA), rheumatoid factor (RF), paraneoplastic and related antibodies (CV2/CRMP-5, ACh receptor, PCA-Tr, ANNA-3, PCA-2, anti-Hu [ANNA-1], and amphiphysin), antivoltage-gated potassium channel complex [VGKCc] antibody, anti-thyroperoxidase antibody, anti-thyroglobulin antibody (TG), anti-gliadin antibodies, anti-tissue transglutaminase (TTG) antibodies, Lyme antibody, rapid plasma reagin (RPR), and 24-hour urine for heavy metals.…”
Section: Casementioning
confidence: 99%
“…Vascular dementias generally occur in patients who are over 50 years of age and in those with risk factors for vascular disease. 3 …”
Section: Epidemiologymentioning
confidence: 99%